KESIAPSIAGAAN DALAM MENGANTISIPASI BENCANA DI PERPUSTAKAAN DAN PUSAT ARSIP - Sitepu, Apallidya; Armansyah, Cut; S. Saary, Rina; Nani Rahayu, Rochani (BACA: Jurnal Dokumentasi dan Informasi, 2009)
This article covers disaster preparedness, kinds of disaster and its recovery procedures and restoration of library materials and archives damaged caused by flood. Step by step on disaster prevention, disaster preparedness and early warning system are also included in this article.